Money for Nothing and Checks for Free : Recent Developments in U.S. Subprime Mortgage Markets - Mills, Paul.; Kiff, John. (Washington, D.C. : International Monetary Fund, 2007)
After a number of warning signs, the U.S. "subprime mortgage crisis" became a headline issue in February 2007. Notwithstanding the bankruptcy of numerous mortgage companies, historically high delinquencies and foreclosures, and a significant tightening in subprime lending standards, the impact thus far on core U.S. financial institutions has been limited. This paper reviews the history and structure of the subprime market. The results suggest that new origination and funding technology appear to have made the financial system more stable at the expense of undermining the effectiveness of consumer protection regulation. Potential solutions to the management of this trade-off are then explored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet